Interactivation design : places for social imagination and conversation in Lindängelund - Alvaker, Karolina (SLU/Landscape Architecture (until 121231), 2010)
This master project in landscape architecture is named Interactivation Design - places for social imagination and conversation in Lindängelund. There are two main purposes of this thesis the first being to bring forth a study of interactivity implemented in the subject of landscape architecture. The second purpose of this thesis is to present a proposal to design a confluent landscape weaving together the upcoming botanical garden of Lindängelund and the residential area of Almvik, both situated in southern Malmö, Sweden, and also weaves people and their experiences together. This project may be described as investigative and experimentative reaserch by design. The first part of this project, Interactivation, is consisting of a theoretical report which discusses different ways of approaching when, how and why we interact in public space. Literature studies in for example space, placemaking, social life, people, participation and Japanese emptiness concepts has been undertaken to gain knowledge in the aim to create interactive landscape design. The second part, Context and Design Proposal, introduces the project context area of Southern Fosie in Malmö which consists of different kinds of residential areas, people of different nationalities and a large building site for a botanical garden and recreational area. An introductory analysis of the context is followed by a presentation of the design process showing how theories and inspirations lead to interactive solutions. Finally a design proposal for an interactivation park in southern Almvik Park is presented together with detailed descriptions of features and with design solutions aiming to bring forth a physical as well as mental interactive experience for the park user. The third and concluding part, Reflective Analysis, is a discussion of the work and results of this project. This last part of the project ties the tree parts together into a complete whole as it is about whether the proposal can be led back to the theory. It is my aim to bring forth this thesis as a suggestion of how an interactivation design process may proceed and I hope that it will become an inspirational source for students, landscape architects, urban intressents and others. I hope that the discussion about interactivation design will not end here but instead go on. Keywords: interactivation, interactive, landscape architecture, landscape design, urban design, public space, relation, experience, participation, addition